2019
DOI: 10.1186/s41155-019-0117-4
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation of fear of missing out scale (FoMOs): Turkish version validity and reliability study

Abstract: Background: The aim of this study is to examine psychometric properties of the Turkish version of the fear of missing out scale (FoMOs) on three different study groups. Method: We conducted the construct validity of the Turkish FoMOs with confirmatory factor analysis, measurement invariance (study I; n = 354), and concurrent validity (study II; n = 371). We also evaluated the reliability of the Turkish FoMOs (study III; n = 61) using test-retest and Cronbach alpha reliability. Results: In study I, the confirma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 33 publications
(42 reference statements)
2
27
0
6
Order By: Relevance
“…A total score was calculated by averaging the scores, with higher mean scores indicating a greater level of FoMO. This instrument has demonstrated good construct validity [ 162 , 163 ], and good internal consistency with Cronbach’s alphas of α = 0.93 [ 164 ] and 0.87 [ 64 ] with α = 0.87 in the present study.…”
Section: Methodsmentioning
confidence: 75%
“…A total score was calculated by averaging the scores, with higher mean scores indicating a greater level of FoMO. This instrument has demonstrated good construct validity [ 162 , 163 ], and good internal consistency with Cronbach’s alphas of α = 0.93 [ 164 ] and 0.87 [ 64 ] with α = 0.87 in the present study.…”
Section: Methodsmentioning
confidence: 75%
“…Specifically, FOMO has shown mild to moderate inverse correlations with life satisfaction. 26 , 66 , 69 Furthermore, mild to moderate inverse associations have been found between FOMO and emotional well-being. 42 , 85 …”
Section: Negative Affectivity and Demographicsmentioning
confidence: 95%
“…Some work has tested and found support for a single latent dimension. 26 - 28 Wegmann et al 23 added the previously described state-based content to the Przybylski et al 1 FOMO Scale and refined it through exploratory factor analysis with a sample of German participants. They then validated the expanded scale with confirmatory factor analysis in a separate German sample, revealing a two-dimensional model involving trait- and state-based FOMO factors.…”
Section: Background Definition and Measurement Of Fomomentioning
confidence: 99%
“…The results of previous studies showed that the reliability of internal consistency and test-retest reliability of different versions of the FoMOs were good but that the structural validity was inconsistent. Specifically, the Turkish 16 and Spanish 18 versions of the FoMOs showed a one-factor structure supporting the original English version structure with good internal consistency (αs > .85). However, the Italian 19 version of the FoMOs showed a two-factor structure, and the data fit a two-dimensional model better with proper internal consistency (αs > .73).…”
Section: Introductionmentioning
confidence: 68%
“…The Fear of Missing Out scale (FoMOs), the most widely used validated instrument in psychological studies to measure individuals' general FoMO 3,12,13 ; it is a self-report questionnaire that was developed by Przybylski et al (2013) based on self-determination theory 14 . The FoMOs has been translated to Turkish 15,16 , Arabic 17 , Spanish 18 , and Italian 19 . The results of previous studies showed that the reliability of internal consistency and test-retest reliability of different versions of the FoMOs were good but that the structural validity was inconsistent.…”
Section: Introductionmentioning
confidence: 99%